THE RELATIONSHIP OF FAMILY ROLE IN FULFILLING HUMAN BASIC NEEDS WITH SELF-CONCEPT AMONG POST STROKE PATIENTS AT PUSKESMAS SINDANG BARANG BOGOR : HUBUNGAN PERAN KELUARGA DALAM PEMENUHAN KEBUTUHAN DASAR MANUSIA DENGAN KONSEP DIRI PASIEN PASCA STROKE DI PUSKESMAS SINDANG BARANG KOTA BOGOR - Julianto Laia (Wijaya Husada, 2018)
Background : Stroke is a health issue and needs spesial attention. Based on the basic health research, stroke is a major couse of death and disability in almost all hospitals in indonesia. Organizations stroke world accouting for nearly 85% of people who have the risk factors can prevent a stroke if aware of and andress theserisk factors early on. The role of the family will help the patient care process to make the best possible stroke patients can do the activity again while not fully back to normal as before the stroke. The concept of human beings have a role in the fulfillment of basic needs. A positive self concept gives meaning and unity to someone. Healthy concept generates positive feelings toward themselves. The Objectiveof this research : To determine the relationship role of the family in the fulfillment of basic human needs with the self-concept among post stroke patients in the Sindang Barang Bogor. The Methods : This study used a descriptive analytical design and cross sectional approach. The technique used in this research is total sampling with the number of sample 46 respondents. The collection of data obtained through questionnaires. The Results : Based on the analysis of the relationship between the role of the family with self-concept of 46 respondents (67,4%) had the role of a passive family with poor self-concept as much as 20 respondents ( 43,5 %). The Results of statistical test p value = 0,016 which means p value < 0,05 means Ho rejected shows that there is a significant relationship between relationship role of the family in the fulfillment of basic human needs with the self concept post stroke patients.